MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS II PADA MATA PELAJARAN MATEMATIKA MELALUI PENDEKATAN TaRL (Teaching at the Right Level) DI SDN 20 MATARAM - Suryanti; Husniati; Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the learning outcomes of grade II students of SDN 20 Mataram through the TaRL (Teaching at the Right Level) approach in Mathematics. Mathematics is a scary subject and is considered difficult by students who are raised because of the inability of students to solve problems related to calculations and analysis such as multiplication, division, fractions, or mathematical symbols. Moreover, SDN 20 Mataram is an inclusive school that has more than 2 inclusive students or ABK (Children with Special Needs) in each class. This is certainly a concern for teachers to determine learning strategies in the classroom. The design of this study was carried out in 2 cycles with four important components, namely planning, implementation, observation, and reflection. Participants in this study were all grade II students as many as 9 male students. This study used data collection techniques, observation and tests and data analysis techniques used were descriptive quantitative. The research results obtained in cycle I participants were 3 students who completed the course with a percentage of 33%, while 6 students who did not complete or did not meet the KKM (70) were 6 students with a percentage of 67% of the total number of 9 students. In cycle II, 7 students completed the course with a percentage of 78%, while 2 students did not complete the course with a percentage of 22%. Thus, it can be concluded that through the TaRL approach (Teaching at the Right Level) can improve student learning outcomes in Mathematics subjects.